Concierge Excellent Service to Increase Customer Satisfaction - I Made Adi Dwi Cahyana Putra; I Gusti Made Wendri; I Putu Budiarta (Catuspata Press, 2020)
Purpose: This research aims to improve the concierge's excellent service in increasing guest satisfaction at a 5 star hotel in Legian tourist area, Kuta, Badung, Bali, Indonesia. Research methods: Data are analyzed using the theory of Service Quality (SERVQUAL) and Importance Performance Analysis which is described in the Cartesian diagram. Findings: There are negative and positive gaps between guest perceptions and expectations. The attribute that has a negative gap is the X2 variable regarding the cleanliness of the concierge area. Implication: The hotel needs to improve cleanliness of the concierge area, the ability of the concierge to carry on the promised service on time, and suitability of information needed.